THE EFFECT OF QUANTUM LEARNING ON THE STUDENTS’ ACHIEVEMENT IN WRITING ARGUMENTATION - Sagita Kristiani; Amrin Saragih (Universitas Negeri Medan, 2012)
ABSTRACT This study was aimed at finding out the effect of applying Quantum Learning on the Students’ Achievement in Writing Argumentation. The objective of the study was to find out whether the application of Writing Argumentation. This study used the experimental method. The population was the 2010/2011 third year students of SMA N.1 DOLOK BATU NANGGAR, totally 240 students. The sample was 60 students of randomly chosen as the representative of population. They were divided into two groups. The first group (experimental group) was taught by applying Quantum Learning while the second group (control group) was taught with conventional method. The test was divided into two groups, pre- test and post- test. The instrument used in this study was a writing test. The data were analyzed by using t-test. T-observerd was 3.75 and the t-table was 2.000 (p=0.05). The result of the analysis shows that the value of the t- table (3.75> 2.000; p= 0.05), it could be consulted that Quantum Learning has significant effect on the teaching argumentative writing. Key Word: Quantum Learning, Writing, Argumentation